Clinicopathological Analysis of 34 Cases of Primary Antineutrophil Cytoplasmic Antibody-Associated Vasculitis in Chinese Children - Wu, Jingyi; Pei, Yuxin; Rong, Liping; Zhuang, Hongjie; Zeng, Shuhan; Chen, Lizhi; Jiang, Xiaoyun (Frontiers in Pediatrics, 2021)
Background: To summarize the clinicopathological features and prognostic risk factors of primary antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV) in children. Methods: Clinical and prognostic data for children admitted to our center with AAV between September 2003 and September 2020 were studied retrospectively. The incidence and risk factors of end-stage renal disease (ESRD) was calculated and analyzed. Results: Thirty-four children were enrolled; 28 were female, with a median onset-age of 10 years old. Except for 1 case negative for ANCA, the other 33 patients were diagnosed with MPA. The most frequently involved organ was renal (100.0%), followed by lung (58.8%) and heart (50.0%). Twenty children (58.8%) progressed to ESRD with a median course of 3 months, and they were more likely to present respiratory and cardiovascular system involvement compared to the non-ESRD group (p<0.05). Patients in the ESRD group also had a higher serum creatinine level, 24-hour protein excretion, PVAS, and a lower level of eGFR, hemoglobin, and complement C3 compared to those in the non-ESRD group (p<0.05). The main pathological manifestations were crescentic and sclerotic in the ESRD group and focal in the non-ESRD group. After six months of induction therapy, 90.0% of cases achieved complete or partial remission. The multivariate logistic regression model showed that baseline eGFR<60 ml/min/1.73 m2 was an independent risk factor for progressing to ESRD (OR=0.016, 95%CI =0.001~0.412, P=0.012). Conclusions: AAV in children usually occurs in teenage girls, and the most common involved organ is kidney, of which hematuria is the most common symptom, followed by proteinuria, abnormal renal function (eGFR<90 ml/min/1.73 m2), et al. The primary type of AAV is MPA. Nearly 60% of patients progressed to ESRD with a median course of 3 months. Baseline eGFR<60 ml/min/1.73 m2 is an independent risk factor for ESRD progression in AAV children.